YTHDF2 regulates the adriamycin (ADM) resistance in NKTCL by modulating the m6A modification of SLC16A9 - Meng Dong; Xudong Zhang; Zeyuan Wang; Yue Zhang; Siyu Qian; Zhenzhen Yang; Shaoxuan Wu; Qing Yang; Xueyi Sun; Mingzhi Zhang; Qingjiang Chen (Translational Oncology)
Context: Natural killer/T-cell lymphoma (NKTCL) is an aggressive malignancy with a high propensity for drug resistance, particularly to anthracyclines like adriamycin (ADM). The molecular mechanisms of ADM resistance in NKTCL are not fully understood. Objective: In this study, we aimed to elucidate the role of YTHDF2 in the regulation of SLC16A9 mRNA stability and its implications in ADM resistance in NKTCL. Materials & methods: The study examined the expression changes of SLC16A9 under varying concentrations of ADM and manipulated the expression levels of SLC16A9 and YTHDF2 through overexpression and knockdown. By analyzing the levels of m6A modification, it was revealed that YTHDF2 regulates SLC16A9 expression via the m6A pathway, thereby influencing ADM resistance. This conclusion was further validated by in vivo experiments. Results: Our results showed that overexpression of SLC16A9 enhanced ADM resistance, while knockdown of SLC16A9 increased sensitivity to ADM. Further investigation revealed that ADM treatment reduces m6A modification levels on SLC16A9 mRNA, which is associated with decreased binding of YTHDF2 to SLC16A9 mRNA, leading to increased SLC16A9 expression. We also found that overexpression of YTHDF2 reduced SLC16A9 expression and increased ADM sensitivity, whereas knockdown of YTHDF2 had the opposite effect. In vivo experiments using a nude mouse model further confirmed that SLC16A9 knockdown reduces tumor growth and enhances sensitivity to ADM. Conclusions: our study provides direct evidence that YTHDF2 modulates ADM resistance in NKTCL by regulating the m6A modification of SLC16A9. Targeting the YTHDF2-m6A-SLC16A9 axis may offer a novel therapeutic strategy to overcome chemotherapy resistance in NKTCL.